Orientalis dan Studi Sirah Nabawiyyah: Telaah Terhadap Pemikiran Clinton Bennett - Mufid, Abdul (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Orientalists and Sirah Nabawiyyah Studies: An Examination of Clinton Bennett's ThoughtsSirah Nabawiyah is a study that has been mostly carried out by Eastern scholars (insiders) and Western scholars (outsiders). For Muslims, the life history of the Prophet is a source of aspiration and adaptation for practical purposes in social life. Meanwhile for non-Muslims, studying sirah nabawiyah is a source of curiosity in understanding Islam as a successful religion in the past and present. This study aims to explore the views of the British orientalist, Clinton Bennett, who is concerned with the study of Islamic studies in general, and the study of sirah nabawiyah in particular. The research method used is qualitative descriptive-analytical. The academic problem that arises in the form of a research question is how Clinton Bennett views sirah nabawiyah in his work In Search of Muhammad? The results of this study indicate that Clinton Bennett has been neutral and positive when studying the Prophet's biography, although sometimes he cites negative things. Bennett has discussed the Sirah teaching methodology with its various varieties practiced in the western academic world and mentioned various orientalist views which have a critical and sensitive approach to faith. According to him, scientific criticism must be maintained without sacrificing the sensitivity of faith